Berkeley's theory of radical dependence - Jennings, Gavan (Cambridge Scholars Publishing, 2018)
This work traces the theory of Radical Dependence through its various forms in Berkeley's philosophical works. It shows that a desire to establish a theory of Radical Dependence underlies all of these works and that this theory unifies Berkeley's various phases of philosophical development. The work begins by establishing the meaning of "Radical Dependence" and examining the influence of Greek, Early Christian and Mediaeval philosophers and theologians on the development of the concept. Subsequently, the deism of the seventeenth-century philosophers is examined; the influence of science and rat